Economic structure, technology diffusion and convergence: The case of the Italian regions - Matteo Lanzafame (University of Kent, Department of Economics, 2005)
Taking Italy as a case study, this paper investigates the link between economies' structural similarities and convergence. Specifically, treating technology as sector-specific and modelling technological spillovers as a positive function of the degree of similarity between economies' sectoral features, we propose a modified version of the Solow model and derive an extended convergence equation. The latter is then estimated by means of Panel Data procedures and data on the Italian regions over the 1970-1995 period. The results bring empirical support to our approach.
Keywords: O40; R11; 330; Convergence; Technology Diffusion; Regional Growth; Italy